Graduate entry to nursing: An exploration of the demographic characteristics of New Zealand students. (October 2020) - Jamieson, Isabel; Norris, Kate; Short, Kylie; Papps, Elaine; Dixon, Alison
Abstract: This paper describes the characteristics of student enrolled in New Zealand's first Graduate Entry to Practice (GEN) programme. Data were collected from students enrolled in the first five cohorts of the programme from 2014 to 2018 (n = 93). In total 69 students responded to an on-line, self-report survey, resulting in a 74% return rate. The majority of respondents were female (87%, n = 60), aged 21–30 (68%, n = 47) and New Zealand European (77%, n = 53). The educational background of respondents ranged from theology, to marine biology and more commonly science based degrees. Their motivation for entering nursing was to work in a diverse and caring profession with many wanting to eventually move to advanced practice roles. A key finding was that the students considered that the primary role of the nurse was the provision of holistic care to both the patient and their family. The majority wish to start their nursing careers in the acute hospital based areas of care provision. Highlights: Accelerated graduate entry programmes for nursing are new in the New Zealand context. GNE programmes appear to attract mature students to nursing who may not have otherwise considered entering the profession. Many students are planning to move to advanced practiced base roles such as nurse practitioner.